Correlation of radio- and histomorphological pattern of pulmonary adenocarcinoma - Lederlin, Mathieu; Puderbach, Michael; Muley, Thomas; Schnabel, Philipp Albert; Stenzinger, Albrecht; Kauczor, Hans-Ulrich; Heußel, Claus Peter; Herth, Felix; Hoffmann, Hans; Dienemann, Hendrik; Weichert, Wilko; Warth, Arne (The European respiratory journal, 2013)
Recently, a novel classification system based on tumour architecture and with high prognostic impact has been proposed for pulmonary adenocarcinomas (ADCs). For imaging-based prediction of histological ADC subtypes and, thus, prognosis, it is of paramount importance to investigate the correlations of radio- and histomorphological parameters. Associations between histomorphological ADC growth patterns (lepidic, acinar, papillary, micropapillary and solid) and data from pre-operative assessment by computed tomography (CT) imaging of 174 resected pulmonary ADCs were analysed. Margin configuration as well as solidity/ground glass opacity of an ADC was associated with distinct histomorphological ADC growth patterns. Solid-predominant ADCs usually had smooth margins and were also solid in CT scans, while lepidic-predominant ADCs had no predominant margin pattern, were located in the periphery, showed a positive bronchogram and were frequently associated with solidity/ground glass opacity. In addition, nonspherical tumour growth was a negative predictor of overall and disease-specific patient survival. We defined CT morphological parameters that were associated with histomorphological growth patterns of pulmonary ADCs. These data may form the basis for the development of future prognostic algorithms in the palliative setting, which include an integrated evaluation of biopsy histomorphology and CT scan morphology of nonresectable pulmonary ADC.